Développement et validation d’un questionnaire évaluant les attitudes socio-affectives en maths - Philippe A. Genoud; Matthias Guillod (Recherches en Éducation)
The goal of this study is the construction and the validation of a new instrument for the assessment of students’ socio-affective attitudes towards mathematics. The questionnaire is organized around the three facets of attitudes (cognitive, affective and behavioral components) and includes a normative measure. It is formed of eight scales (45 items in all) assessing various beliefs about mathematics: perceived utility, self-concept, controllability, positive and negative affects, affective regulation, investment, and masculinity of mathematics. Results attest the quality of the psychometric properties of the instrument, including internal consistency, temporal stability, as well as its structure tested using a confirmatory factorial analysis. The questionnaire is ready to be used with students (secondary school) and allows for the assessment of their general attitudes towards mathematics. It can be combined with complementary measures focusing on specific activities and tasks.